COMPARISON OF CHEMICAL COMPOSITION AND ANTIBACTERIAL ACTIVITY OF MENTHA PULEGIUM ESSENTIAL OIL FROM TWO ECOTYPES (EL BAYADH AND DJELFA) - Z., . Boukhobza1; A., Cheriti1*; M., Kacimi El Hassani2; M. B., Lahreche2 (university of eloued جامعة الوادي, 2019)
Mentha pulegium, collected from two different sites in Algerian high plains (El Bayadh and Djelfa), were analyzed to determine essential oil constituency. Essential oils were extracted by hydrodistillation and subsequently analyzed by GC/MS. Quantitative differences were recorded between the percentages of some constituents between plants from the two geographical origin. The most important major components were: 1,8-cineole, menthone, menthol, cis-Pulegone and Pulegone. The antimicrobial activity of the essential oils was tested using the disc-diffusion assay. The results showed that the essential oil of Mentha pulegium had great potential of antibacterial activity against selected bacteria
artical
Keywords: Essential oil; Mentha pulegium; GC/MS; antibacterial activity; ecotypes; high plains.